Liquid phase catalytic hydrogenation reduction of Cr(VI) using highly stable and active Pd/CNT catalysts coated by N-doped carbon. (February 2019) - Li, Minghui; He, Jiao; Tang, Yuqiong; Sun, Jingya; Fu, Heyun; Wan, Yuqiu; Qu, Xiaolei; Xu, Zhaoyi; Zheng, Shourong
Abstract: Liquid catalytic hydrogenation is a green and cost-effective technique for the reductive removal of pollutants in water. Supported noble metals are the most frequently used catalysts in liquid phase catalytic hydrogenation, whereas marked catalyst deactivation is commonly identified. In this study, we coated supported Pd catalyst on carbon nanotube (denoted as Pd/CNT) by different overcoatings (including SiO2, carbon and N-doped carbon) to prevent catalyst deactivation. The activities of the coated catalysts for liquid phase catalytic hydrogenation reduction of hexavalent chromium (Cr(VI)) differed with the overcoating properties. Negligible Cr(VI) conversion was observed on SiO2 coated Pd/CNT, while feasible Cr(VI) reduction was identified on carbon coated (denoted as Pd/CNT@C) and N-doped carbon coated catalysts (denoted as Pd/CNT@CN). Pd/CNT@CN exhibited a much higher catalytic activity than Pd/CNT@C, which was ascribed to the stronger Cr(VI) adsorption on CN overcoating. The catalytic activity of Pd/CNT@CN was positively correlated with the conductivity and hydrophilicity of CN overcoating, which could be optimized by varying carbonization temperature. Furthermore, Pd/CNT@CN retained its initial activity after ten consecutive catalyst cycles without any deactivation, whereas Pd/CNT only retained 8.2% of its initial activity, reflecting much higher catalytic stability of Pd/CNT@CN than Pd/CNT. The findings in the present study highlight that liquid catalytic reduction using Pd/CNT@CN as the catalyst is a highly stable and effective method to remove Cr(VI) in water. Graphical abstract: Highlights: Pd supported on carbon nanotubes was coated by overcoatings for Cr(VI) reduction. Coating by N-doped carbon (CN) enhanced stability of supported Pd catalyst. CN coated Pd catalyst had a higher catalytic activity than other coated catalysts.